Touristically-attractive springs in the Polish Lowlands - Girjatowicz, Józef P. (Turyzm/Tourism, 2013)
On the basis of available published materials and his own research, the author identifies the 27 most attractive springs in the Polish Lowlands. He describes their most important landscape and tourism assets – the relief of the spring outlet area, landforms, the character of the spring itself and the accompanying tourism infrastructure. The article presents available data regarding the water discharged by the springs: volume, temperature, colour and medicinal properties; as well as pointing to associated interesting natural features, examples of religious architecture and historical curiosities. The distribution of springs in the Polish Lowlands is uneven, with the majority found in the area of the morainic uplands, as well as in deeper river valleys and lake troughs.